The Influence of Mathematical Anxiety and Self-Concept on Students' Mathematics Learning Outcomes - Setiani, Leli; Lubis, Nur Ainun (Universitas Ma'arif Lampung, 2024)
Mathematical anxiety and self-concept are factors that influence students' mathematics learning outcomes. Therefore, this research aims to determine the influence of mathematical anxiety and self-concept on the mathematics learning outcomes of class VIII students at MTs Miftahul Ula partially and simultaneously—a type of ex post facto research with a quantitative approach. The population in this study consisted of all VIII class students at MTs Miftahul Ula for the 2023/2024 academic year, totaling 70 students consisting of 2 classes. The sampling technique is carried out using a saturated sampling technique, namely a sampling technique where all members of the population are used as samples without giving each element or member of the population the same opportunity to become a sample. Based on the results of data analysis, it was found that the significant value for mathematical anxiety was and the significant value for self-concept was . The mathematical anxiety factor only partially influences students' mathematics learning outcomes. Meanwhile, based on the F test, the value was three, and the significant value was . So, there is an influence between mathematical anxiety and self-concept on students' mathematics learning outcomes.